Implementation of Da'wah Management in Improving the Quality of Hajj Manasik Services at KBIHU ANNUR Kudus - Nur Ahmad; Nurul Hidayati (Darul Yasin Al Sys, 2026)
Systematic management of hajj guidance services is essential for preparing pilgrims who possess the knowledge, practical competence, spiritual readiness, and independence required to perform the pilgrimage. This study analyzed the implementation of da‘wah management through planning, organizing, actuating, and controlling functions in supporting the quality of hajj guidance services at KBIHU ANNUR Kudus. A qualitative field-research design was employed. Data were collected through semi-structured interviews, observations, and documentation involving KBIHU managers, field coordinators, administrative staff, and prospective pilgrims selected through purposive sampling. The data were analyzed using the Miles and Huberman interactive model, comprising data reduction, data display, and conclusion drawing and verification. Source and technique triangulation was employed to enhance data validity. The findings demonstrate that da‘wah management was implemented through an integrated and continuous process. Planning involved comprehensive planning and coordination meetings. Organizing and actuating comprised the systematic preparation of guidance materials, theoretical and practical training, health and spiritual guidance, group formation, and assistance in Makkah and Madinah. Controlling was undertaken through evaluations, question-and-answer sessions, coordination, and continuous monitoring of pilgrims. These practices indicate that service quality extended beyond the transmission of religious knowledge to encompass pilgrims’ practical skills, spiritual preparedness, and independence. The study concludes that integrated da‘wah management provides an organizational framework for comprehensive and sustainable hajj guidance oriented toward pilgrim independence. Theoretically, the findings extend da‘wah management scholarship into the context of hajj guidance; practically, they provide a reference for KBIHU managers in developing integrated service programs. Future studies should examine multiple KBIHUs using mixed methods to assess service quality, pilgrim satisfaction, and independence more comprehensively.